PEMANFAATAN TEKNOLOGI INFORMASI DALAM PEMBELAJARAN AGAMA HINDU DI SMAN-1 KUALA KAPUAS - Ni Putu Eka Merliana (Jurusan Dharma Acarya STAHN-TP Palangka Raya, 2020)
The purpose of this study is to find out 1) the use of information technology in the learning of Hinduism, 2) what factors support the use of information technology in learning Hinduism, 3) the obstacles experienced by the SMAN-1 Kuala Kapuas in utilizing information technology in religious learning Hindu. SMAN-1 Kuala Kapuas being the first high school in the Kapuas district of Central Kalimantan Province has implemented technology as a medium of learning and this has also been applied in Hindu learning. The results obtained from this research are the application of information technology has a positive influence on students, where students are able to deeply understand the material provided in the teaching and learning process. The importance of technology in learning Hinduism makes the character of Hindu students at SMAN-1 Kuala Kapuas better so that they can implement it in their daily lives.